TEOLOGI PUBLIK DAN PRAKSIS PENGEMBANGANYA DALAM PASTORAL PARIWISATA DI KEUSKUPAN RUTENG - Benediktus Denar & Paulus Tolo (STIPAS St. Sirilus Ruteng, 2022)
This article specifically describes the model of public theology development played by the Catholic Church of the Diocese of Ruteng in responding to the destructive impacts of tourism development in Labuan Bajo - West Flores. The main issue that will be described in this article is that there are a number of destructive impacts in the development of the Labuan Bajo tourism industry that sacrifice the interests and lives of local people. The development of Labuan Bajo tourism only provides benefits for business actors and state actors, while the local community must bear the burden of destruction due to tourism development. On the other hand, the public role of the Church has not been so significant. The research method used to elaborate this article is a qualitative study with a contextual theological paradigm and approach. The results of the study conclude that the public role of the Church by prioritizing the concepts and messages of public theology is very important for establishing a just tourism development model, especially for the local community in Labuan Bajo.